Ochrona lasów w prawie Unii Europejskiej - Kalicka-Mikołajczyk, Adriana (Leśne Prace Badawcze, 2019)
An estimated 5% of the world’s forests are located in the EU and these forests have continuously expanded for over 60 years, although recently at a lower rate. Forests and other wooded land now cover 155 million hectares and 21 million hectares, respectively, together more than 42% of the EU land area. Although the treaties in the European Union contain no provisions for a common forest policy, there is a long history of EU measures supporting forest and forest-related activities coordinatedwith member states, mainly through the Standing Forestry Committee. For several decades now, environmental forest functions have attracted increasing attention mostly in relation to the protection of biodiversity and, more recently, in the context of climate change. The main objective of this paper was twofold: first, to identify the EU legislation directly and indirectly connected to forest protection, and second, to determine its legal character and effectiveness. In conclusion, in recent years the EU has adopted numerous regulations that are directly and indirectly connected to forests and they can be divided into two groups: internal and international acts. Moreover, we can distinguish legally binding acts such as regulations, directives as well as international agreements and soft law acts including strategies, green books, communications, action plans or declarations.